Tinjauan Yuridis Terhadap Penyalahgunaan Perjanjian Kerja Waktu Tertentu (PKWT) Untuk Pekerjaan Yang Bersifat Tetap Berdasarkan Undang-Undang Cipta Kerja - Ulvina Suci Kartika; Dian Utari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Fixed-Term Employment Agreements (Perjanjian Kerja Waktu Tertentu/PKWT) are often applied to permanent jobs, creating uncertainty in employment status and weakening legal protection for workers. This study analyzes the legal framework governing PKWT, its misuse in permanent employment, and its legal implications for worker protection. The research employs a normative juridical method using statutory, conceptual, and case approaches based on primary, secondary, and tertiary legal materials. The findings show that Law Number 6 of 2023 on Job Creation and Government Regulation Number 35 of 2021 restrict PKWT to temporary or fixed-term work. The use of PKWT for permanent jobs violates these provisions, resulting in the conversion of the employment relationship into an Indefinite-Term Employment Agreement (PKWTT), the recognition of permanent workers' rights, and legal liability for employers. The misuse of PKWT also reduces job security and legal protection for workers. This study highlights the importance of strengthening regulatory enforcement to ensure effective legal protection for workers. Keywords: Fixed-Term Employment Agreement (PKWT), Permanent Employment, Legal Protection of Workers